Investigation of engineering characteristics of mardin stone used in eco-building. Issue 1 (31st December 2016) - Sarıışık, A.; Sarıışık, G.
Abstract: The engineering characteristics of samples obtained from Mardin stone were investigated. Natural stones that are produced in the Yalım village quarries, which are close to the Mardin citycentre, are popular among the public and commonly used as a building construction component. A series of engineering characterization tests and analyses (mineralogical and petrographic characteristics; chemical, physical, mechanical, andinsulation properties) were conducted on the Mardin stone samples. The structure of the Mardin stone was largely composed of micritic and crystallized calcite (>95%). The porosity ratio was 22.16%, the sound speed was 3.270 m/s, the specific mass was 2.680 kg/m 3, the Knoop hardness was 120 HK, and the water absorption capacity was 13.72%. Other findings included a compressive strength of 20 MPa, compression strength after frost of 15.58 MPa, schmidt hardness of 33.1 MPa, SO2 abrasion resistance in a humid environment of 1.54%, and flexural strength of 3.73 MPa. The stone showed 0.04% resistance to ageing by thermal shock, 0.78% resistance to salt crystallization, and 45.46 mm resistance to abrasion. According to the analysis, the value of thermal conductivity, another important characteristic of the Mardin stone, was 0.72 W/mK. This value was better than those of other natural stones. The highest thermal insulation performance was determined in the stone samples with high porosity and low thermal conductivity values. The results suggest that Mardin stonesare suitable for architectural restoration and eco-building.